Prominent peaks and social discourses of the 2023 Escalation in the Ongoing Israel–Hamas armed conflict - Reuben Ng; Ting Yu Joanne Chow (PLoS ONE, 2025)
Background This paper investigates the sharp increase in media posts and engagement surrounding the initial four months (October 2023–January 2024) of the Israel–Hamas armed conflict, following the inciting incident of a surprise militant attack launched on 7 October 2023. The impetus for documenting the trajectory of social media conversations lies in capturing and cataloging the biggest drivers of engagement, public sentiments and groundswell themes, reflecting the public zeitgeist during a period of uncertainty. Objectives Few big data studies have delved into initial public discourse surrounding the escalation of the ongoing conflict. First, we identify the biggest generators of buzz, proxied by spikes in mention-counts; secondly, we identify content trends proxied by quantitative sentiment valence, top keywords and emojis, and qualitatively outline the biggest generators of media engagement via top engagement metrics (likes, reposts). Methods We analyse a large corpus of publicly-available content from online platforms (Twitter, Reddit, Tiktok) obtained using academic-level API access, containing search terms: Palestine, Palestinian(s), Israel(i)(s), Gaza, Hamas. Our first research aim utilizes a prominent peaks model (upper-quartile significance threshold of prominence>1,500,000). Our second research aim utilized qualitative analysis on valence, top keywords and emojis, and top themes. Results Eight prominent peaks were identified, finding that news about violence (e.g., airstrikes, citizen harm), groundswell movements (e.g., international activism like worldwide strikes, protests and marches, awareness movements, and outrage in response to current conditions) and politically-charged happenings (e.g., missile strikes) had the biggest hand in boosting discoursal spikes. Valence scores were generally negative, following a general monthly distribution of negative (59%), neutral (31%), and positive (10%), with main keywords focused on terror, violence, and calls for ceasefire. Qualitatively, we find salient groundswell movements (e.g., e-sims for Gaza, content creator strikes for Palestine, circulation of boycott consumer brand lists, co-option of the watermelon emoji as shorthand for support for the cause) and find that the online space is dominated by a fixation on celebrity opinions on the conflict and the circulation of gory footage. Conclusions Overall, emergent public chatter worryingly peaks in response to incendiary news about violence, gory footage and celebrity opinions, though discoursal spikes are also slanted toward groundswell movements of goodwill.